2013
DOI: 10.1007/s00270-013-0771-3
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Inserted External Catheters and Totally Implantable Ports for the Delivery of Chemotherapy: A Systematic Review and Meta-Analysis of Device-Related Complications

Abstract: The findings of this study showed that totally implantable ports are superior to external catheters in terms of catheter-associated complications. However, a formal health technology assessment on the clinical and cost-effectiveness of the use of implantable ports compared with external catheters is needed to inform policy makers of the relative value of investing in totally implantable devices compared with external catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
(52 reference statements)
2
24
0
Order By: Relevance
“…In other patient populations, the catheter type may contribute to the risk; for example, some studies of patients receiving PN found that the risk of CLABSI was higher in those with ports than in those with external CVCs, 6 8 but others have found the opposite 9 – 11 or no apparent difference 12 14 . Because previous studies have shown that pediatric oncology patients with ports have a much lower rate of catheter‐related complications than do those with external CVCs, the use of ports is preferred where feasible 1 , 15 17 . However, the effect of CVC type on the relative risk of complications in pediatric oncology patients during PN administration has not been well explored, so there is insufficient evidence to guide CVC choice in that setting 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In other patient populations, the catheter type may contribute to the risk; for example, some studies of patients receiving PN found that the risk of CLABSI was higher in those with ports than in those with external CVCs, 6 8 but others have found the opposite 9 – 11 or no apparent difference 12 14 . Because previous studies have shown that pediatric oncology patients with ports have a much lower rate of catheter‐related complications than do those with external CVCs, the use of ports is preferred where feasible 1 , 15 17 . However, the effect of CVC type on the relative risk of complications in pediatric oncology patients during PN administration has not been well explored, so there is insufficient evidence to guide CVC choice in that setting 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A nested qualitative study in a larger RCT serves to provide in-depth, explanatory information to inform the main trial, provide additional explanatory information on the findings and to incorporate patient and service user involvement in the research. A systematic review and meta-analysis evaluating the risks of complications associated with centrally inserted external catheters compared with totally implantable Ports in patients undergoing chemotherapy showed that totally implantable Ports are superior to external catheters in terms of catheter-associated complications (3). The National Institute for Health Research Health Technology Assessment Programme has commissioned the Cancer and Venous Access (CAVA) study (4), the first RCT to compare the clinical and cost-effectiveness of three venous access devices for chemotherapy delivery; tunnelled-cuffed central catheters, peripherally inserted central catheters (PICCs) and implantable chest wall Ports (Ports).…”
Section: Introductionmentioning
confidence: 99%
“…Kulkarni et al implied that there was an increased risk of infection, non-infectious complication, and complication-related device removal among patients with CIEVC compared with those with totally implantable ports albeit with some caveats. The reported risk of infection varied substantially between individual studies, and this remained the case irrespective of study type and population (1).…”
Section: Discussionmentioning
confidence: 95%
“…Centrally inserted central venous catheters (CICCs) were introduced in the 1970s and modifications like the Dacron cuff by Hickman in 1979 aided in the improvement of their durability (1). The CICCs are commonly utilized to establish a prolonged route of intravenous (IV) access in both acute or home care settings.…”
mentioning
confidence: 99%